"Determinants of antibiotic use/misuse from patients' and health providers' perspective - A descriptive analysis from coastal Karnataka, India" - Shubhika Jain; Chythra R. Rao; Samarth Goyal (Elsevier, 2024)
Objectives: To evaluate the awareness and practices of patient's antibiotic usage and assess the perception of health providers with regard to antibiotic use and misuse in a tertiary hospital. Methods: A cross sectional study was conducted in a tertiary care hospital in coastal Karnataka, India. The study participants included consenting volunteers of either gender, aged >18 years, including 384 patients, 25 nurses and 25 physicians. Results: Knowledge about indications for antibiotic usage was found to be poor as 85.9 % believed that antibiotics were effective against viral diseases as well. It was found that about 71.6 % patients had self-medicated themselves for minor illnesses, but majority preferred tertiary health care facilities for major illnesses. Practice of the patients was found to be good with 78.1 % patients consulting a physician before consuming antibiotics and 96 % completing the course as advised. Among the 25 nurses interviewed, 92 % reported discussion with patients regarding their antibiotic prescription. About 21.4 % nurses reported to have prescribed antibiotics to other friends, neighbours and patients, on the basis of their clinical exposure. The causes of emerging Antimicrobial Resistance (AMR) as reported by the doctors were-inappropriate prescription, self-medication, and non-adherence to the course as prescribed. Conclusion: Better doctor patient communication, educating both doctors and patients, antibiotic sensitivity-based prescription and practicing evidence-based medicine are required to combat antimicrobial resistance.